2016
DOI: 10.1111/aos.13106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macular pigment and serum lutein concentration changes between free lutein and lutein esters supplements in Japanese subjects

Abstract: The serum lutein concentrations and MPOD levels increased significantly with either free lutein or lutein esters, and no significant differences were found between the two. Both were considered useful as lutein supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(68 reference statements)
1
15
1
Order By: Relevance
“…Two RCTs of supplements ( 48 , 50 ), 4 non-RCTs ( 54–56 , 64 ), and 3 single-arm trials ( 57 , 60 , 61 ) evaluated a supplement with ≥20 mg/d of lutein/zeaxanthin in ≥1 of their study arms. Follow-up in these trials ranged between 2 and 12 mo.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs of supplements ( 48 , 50 ), 4 non-RCTs ( 54–56 , 64 ), and 3 single-arm trials ( 57 , 60 , 61 ) evaluated a supplement with ≥20 mg/d of lutein/zeaxanthin in ≥1 of their study arms. Follow-up in these trials ranged between 2 and 12 mo.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that MPOD is related to the nutritional xanthophyll status and that dietary treatment with xanthophylls increases MPOD [6,14,40] . Epidemiological studies indicate that a higher MPOD may be associated with a lower risk to develop AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate dietary supply with xanthophylls increases MP optical density (MPOD) and exerts beneficial effects in patients with age-related macular degeneration (AMD) [7][8][9][10][11][12][13][14] . Main nutritional sources for xanthophylls are vegetables, egg yolk, fish, and dietary supplements delivering mainly lutein from nonedible plants.…”
mentioning
confidence: 99%
“…A few studies have suggested that the intestinal absorption of xanthophylls is increased in subjects fed xanthophyll esters rather than unesterified xanthophylls while others have shown equivalent bioavailability of both forms when fed to humans . Moreover, only free xanthophylls were present in the plasma of individuals after feeding of either dietary form.…”
Section: Intestinal Absorption Of Vitamin a And Carotenoidsmentioning
confidence: 99%